ANALISIS OF REPEAT ORDER DECISION ON NYUZUU ENTREPRENEURSHIP THROUGH CUSTOMER SATISFACTION, SERVICE QUALITY AND PRODUCT QUALITY - Iwang Suwangsih (Accounting Study Program, Universitas Ciputra Surabaya, 2021)
The purpose of this study to analyze the repeat order decision of the current Nyuzuu beverage products through customer satisfaction, service quality and product quality to NYUZUU’s consumers in Sidoarjo City. The method of this study is quantitave method. The population in this study was 185 consumers (within 2 months), and the sample was 126 respondents. The sampling technique was used purposive sampling. The data obtained were processed using SPSS 16.0 software and analyzed using multiple linear regression analysis. Data collection was obtained by distributing questionnaires. The outcomes of this study are customer satisfaction, and product quality has an important influence in part on repeat order decisions, but service quality has not much. Multiple linear regression analysis shows that the model is Y = 0.569 + 0.548x1 + 0.001x2 + 0.194x3. While the F test results obtained Fcount (34.058)> Ftable (3.15), which means customer satisfaction (X1) and product quality (X3) have a significant effect on repeat order decisions of Nyuzuu products (Y).